Model of Professionalism in Educational Activity: model professionalism pedagogical activity pedagogical competence teaching skills professional self-improvement - Belozerskaya, Svetlana Ivanovna (Psychological Prospects Journal, 2012)
The essence of the concept «model of professional educational activities» is defined. The structural components of this model, characterized by personal and active dentity are analyzed.